Peningkatan Proses Pembelajaran Tematik Terpadu Menggunakan Model Kooperatif Tipe Numbered Head Together di Kelas V Sekolah Dasar - Bima Prakarsa Arzfi; Zainal Abidin (Universitas Negeri Padang, 2021)
The objective of this research is to describe an integrated thematic learning process improvement to the cooperative learning model numbered head together in fifth grade elementary school 11 koto marapak pariaman city. This research by combining a qulititative and quantitative approach. The subjects in this study were class teacher and V class students where there were 7 male students and 5 female students.The research aspects of the teacher first cyclethe average value of 78,13% with sufficient qualification, in the second cycle to 93,75% with excellent qualifications. Aspects of the students' first cycle the average value of 78,13% with sufficient qualification,in the second cycle to 93,75%, with excellent qualifications. Thus the cooperative model of the numbered head together (nht) can enhance the learning process and student learning outcomes.